A Highly Reliable RRAM Physically Unclonable Function Utilizing Post-Process Randomness Source - Lin, Bohan; Pang, Yachuan; Gao, Bin; Tang, Jianshi; Wu, Dong; Chang, Ting-Wei; Lin, Wei-En; Sun, Xiaoyu; Yu, Shimeng; Chang, Meng-Fan; Qian, He; Wu, Huaqiang (IEEE journal of solid-state circuits, 2021)
Physically unclonable function (PUF) has been increasingly used as a promising primitive for hardware security with a wide range of applications in the Internet of Things (IoT). In recent years, novel PUF techniques based on resistive switching mechanism in various emerging nonvolatile memories have demonstrated superior performance on reliability and integration density. In this work, a resistive random access memory (RRAM)-based PUF chip with 8-kb capacity is developed. Two operation modes, namely differential mode and median mode, are embedded on chip. To implement these modes, a current sampling-based sense amplifier is designed to distinguish the current values of the PUF cells and the reference cell. In addition, a split-resistance scheme is proposed to enhance the PUF's reliability significantly. The experiment results show that the differential PUF exhibits excellent performance with native bit error rate (N-BER) below 6 × 10 −6 and inter-Hamming distance (inter-HD) of 49.99%. In the meanwhile, the reconfigurability of PUF challenge-response pairs (CRPs) is demonstrated with 49.77% and 47.29% reconfigure-Hamming distance (reconfigure-HD) in the median mode and the differential mode, respectively.